MENELUSURI DEMURRAGE: EVALUASI OPERASIONAL DAN ADMINISTRATIF DALAM KETERLAMBATAN BONGKAR MUAT KAPAL DI PELABUHAN PT KRAKATAU BANDAR SAMUDERA, CILEGON BANTEN (STUDI KASUS PADA KAPAL MV HUI KANG HAI) - Dewi, Shinta Mardiana; Fifaldyovan, Muhammad Ikhsan; Juniarti, Kurnia (Akademi Pelayaran Nasional Surakarta, 2025)
This study aims to analyze the causal factors behind demurrage incidents during the unloading process of MV Hui Kang Hai at PT Krakatau Bandar Samudera Port, Cilegon, Banten. Demurrage refers to the additional cost incurred due to delays in completing the unloading activities beyond the agreed contract time (laytime). The research applies a mixed-method approach using a case study design, including field observation, in-depth interviews with port operators, and review of technical and administrative documentation. Findings reveal a total delay of 48 hours, resulting in demurrage costs estimated at USD 8,000–10,000 (IDR 128–160 million). The primary contributing factors include inefficiencies in cargo handling labor (25%), delays in document and clearance processes (20.83%), equipment breakdowns (16.67%), and weather disruptions (12.5%). The remaining delays were due to idle time and lack of inter-shift coordination. These findings underscore the urgent need to improve operational monitoring systems, digitize port administration, enhance workforce management, and integrate meteorological data into daily operational planning. This research contributes to strengthening port service systems through data-driven and systemic analysis